A secure and service-oriented network control framework for WiMAX networks. - Lu, Kejie; Yi Qian.; Hsiao-Hwa Chen.
WiMAX, worldwide interoperability for microwave access, is an emerging wireless communication system that can provide broadband access with large-scale coverage. As a cost-effective solution, multihop communication is becoming more and more important to WiMAX systems. To successfully deploy multihop WiMAX networks, security is one of the major challenges that must be addressed. Another crucial issue is how to support different services and applications in WiMAX networks. Since WiMAX is a relatively new standard, very little work has been presented in the literature. In this article we propose a secure and service-oriented network control framework for WiMAX networks. In the design of this framework we consider both the security requirements of the communications and the requirements of potential WiMAX applications that have not been fully addressed previously in the network layer design. The proposed framework consists of two basic components: a service-aware control framework and a unified routing scheme. Besides the design of the framework, we further study a number of key enabling technologies that are important to a practical WiMAX network. Our study can provide a guideline for the design of a more secure and practical WiMAX network.
Keywords: WiMAX networks; Broadband access; Multihop WiMAX networks; Security; Service-oriented network control framework; Unified routing scheme; Wireless communication system; Worldwide interoperability for microwave access